A room-temperature high performance all-solid-state lithium-sulfur battery enabled by a cross-linked copolymer@ceramic hybrid solid electrolyte. (15th December 2022) - Jeon, Eun Ju; Jean-Fulcrand, Annelise; Kwade, Arno; Garnweitner, Georg
Abstract: The use of solid electrolytes (SEs) is a key strategy for enabling the intrinsically safe operation of batteries comprising lithium metal anodes as they suppress the growth of lithium dendrites. Among the different types of SEs, polymer-based hybrid electrolytes (HEs) are highly promising due to their synergetic properties from the constituent polymer matrix and inorganic filler particles. However, the lithium-ion diffusion pathway in HEs is still dominated by the polymer, especially for polyethylene oxide (PEO)-based HEs. The main limitation of PEO is the strong temperature dependence of its ionic conductivity, preventing its use at room temperature (RT). Herein, a cross-linked polymer-based HE with a high ionic conductivity of 1.1 × 10 -3 S cm -1 at RT is presented. The novel cross-linked copolymer, composed of pentaerythritol tetraacrylate (PETEA), tri(ethylene glycol) divinyl ether (TEG), and lithium bis(trifluoromethanesulfonyl)-imide (LiTFSI), serves as a matrix to achieve satisfactory mechanical strength. Integrated Li7 La3 Zr2 O12 (LLZO) particles are covalently bound to the copolymer by a prior surface modification step. To demonstrate the suitability of the developed HE for RT application in advanced battery systems, a solid-state lithium-sulfur cell is built which exhibits an initial specific capacity of 688 mA h g -1 . The ability of this HE to operate at RT can be expected to boost the development of safe all-solid-state batteries for many applications. Graphical Abstract: ga1 Highlights: A hybrid electrolyte based on a cross-linked copolymer with high ionic conductivity at room temperature is presented. The electrochemical properties of the copolymer are enhanced by the incorporation of functionalized LLZO particles. The hybrid electrolyte was applied in an all-solid-state lithium-sulfur battery and operated at room temperature.